Human Milk Oligosaccharide 2′-Fucosyllactose Improves Innate and Adaptive Immunity in an Influenza-Specific Murine Vaccination Model - Xiao, Ling; Leusink-Muis, Thea; Kettelarij, Nienke; van Ark, Ingrid; Blijenberg, Bernadet; Hesen, Nienke A.; Stahl, Bernd; Overbeek, Saskia A.; Garssen, Johan; Folkerts, Gert; van’t Land, Belinda (Frontiers in Immunology, 2018)
Background: Human milk is uniquely suited to provide optimal nutrition and immune protection to infants. Human milk oligosaccharides (HMOS) are structural complex and diverse consisting of short chain and long chain oligosaccharides typically present in a 9:1 ratio. 2’-Fucosyllactose (2’FL) is one of the most prominent short chain oligosaccharides and is associated with anti-infective capacity of human milk. Aim: To determine effect of 2’FL on vaccination responsiveness (both innate and adaptive) in a murine influenza vaccination model and elucidate mechanisms involved. Methods: A dose range of 0.25-5% (w/w) dietary 2’FL was provided to 6-week-old female C57Bl/6JOlaHsd mice two weeks prior primary and booster vaccination until the end of the experiment. Intradermal (i.d.) challenge was performed to measure the vaccine-specific delayed-type hypersensitivity (DTH). Antigen-specific antibody levels in serum as well as immune cell populations within several organs were evaluated using Elisa and flow cytometry respectively. In an ex vivo re-stimulation assay, spleen cells were co-cultured with influenza-loaded bone marrow derived dendritic cells (BMDCs) to study the effects of 2’FL on vaccine-specific CD4+ and CD8+ T-cell proliferation and cytokines secretions. Furthermore, the direct immune regulatory effects of 2’FL were confirmed using in vitro BMDCs T-cell co-cultures. Results: Dietary 2’FL significantly (p<0.05) enhanced vaccine specific DTH responses accompanied by increased serum levels of vaccine-specific IgG1 and IgG2a in a dose-dependent manner. Consistently, increased activation marker (CD27) expression on splenic B cells was detected in mice receiving 2’FL as compared to control mice. Moreover, proliferation of vaccine-specific CD4+ and CD8+ T cells, as well as IFN-γ production after ex vivo re-stimulation were significantly increased in spleen cells of mice receiving 2’FL as compared to control mice, which were in line with changes detected within DC populations. Finally, we confirmed a direct effect of 2’FL on the maturation status and antigen presenting capacity of BMDCs. Conclusion: Dietary intervention with 2’FL improves both humoral as well as cellular immune responses to vaccination in mice, which might be attributed in part to the direct effects of 2’FL on immune cell differentiation.